Reevaluating Point-of-Care Resources: Community Engagement in Difficult Collection Choices. Issue 1 (2nd January 2019) - Walden, Rachel R.; Woodward, Nakia J.; Wallace, Richard L.
Abstract: Rising collection costs sometimes necessitate tough decisions regarding cancellation of popular products. In 2015–2016, the East Tennessee State University Medical Library subscribed to UpToDate and DynaMed Plus, both clinical point-of-care products, with the understanding that one product would be canceled at the fiscal year end. The librarian team undertook a year-long community engagement campaign to inform library users about the pending product cancellation decision. Ultimately, DynaMed Plus was selected and UpToDate was cancelled. The campaign generated user engagement with the decision making, along with perceived benefits including increased awareness of the library's budget constraints, increased discussion of scholarly publishing, and greater faculty/student knowledge of evaluating evidence-based products.